Undernutrition and associated factors among incarcerated people in Bahir Dar and Finote Selam prison sites, Northwest Ethiopia: a cross-sectional study - Hiwot Tesfa; Alemayehu Tarekegn; Mulunesh Alemayehu; Habtamu Temesgen; Hunegnaw Almaw Derseh (BMJ Public Health)
Background Prison is designed with punishment, correction and rehabilitation to the community in mind and these goals may conflict with the aims of healthcare. Incarcerated peoples’ dependency on the prison-limited food menu, inadequate meal provision and poor-quality food increases the risk of malnutrition.Objective To assess the magnitude of undernutrition and associated factors among incarcerated people, Northwest Ethiopia, 2019.Design An institution-based cross-sectional study was conducted in Bahir Dar and Finote Selam prison sites, in Northwest Ethiopia.Methods This study was conducted from 18 March 2019 to 18 April 2019. 475 systematically selected incarcerated people from each prison site were included in this study. Data were collected using structured interviewer-administered questionnaires. A binary logistic regression model was used to identify the associated factors.Results The magnitude of undernutrition among incarcerated people was 19.4%. Not getting family support (adjusted OR (AOR)=3.05, 95% CI=(1.56, 5.96)), not involving with income-generating activities (AOR=2.68, 95% CI=(1.33, 5.40)), diarrhoeal disease (AOR=4.60, 95% CI=(2.14, 9.87)), food allergy (AOR=2.83, 95% CI=(1.47, 5.45)) and chewing khat (AOR=2.93, 95% CI=(1.07, 7.99)) were shown to have a statistically significant association with undernutrition among incarcerated people.Conclusion The burden of undernutrition was high. Various factors contribute to undernutrition such as lack of family support, limited involvement in income-generating activities, diarrhoeal disease, food allergy and a history of chewing khat.